Effectiveness of Acupressure Therapy in Reducing Blood Pressure Hypertension sufferers - Winarto, Edi (Persatuan Dosen Kesehatan Masyarakat, 2023)
Hypertension is a disease that causes complications in sufferers, thereby reducing the sufferer's quality of life. Increased blood pressure in hypertension sufferers can be controlled with pharmacological and non-pharmacological therapy, one of which is using acupressure therapy. This study aims to determine the effectiveness of providing acupressure therapy in reducing blood pressure for hypertension sufferers in the Bukit Raya Village Sub-district Health Center Work Area, East Lampung. This research design is quantitative analytical with a Quasi-Experimental approach using a one group pretest and posttest design. The results of the research conducted showed that the average systolic blood pressure before acupuncture therapy was 168 with a standard deviation of 26.943. After therapy the average blood pressure value decreased to 122 with a standard deviation of 3.535. Meanwhile, the average diastolic blood pressure before acupressure therapy was 103 with a standard deviation of 11.18. After therapy the average blood pressure value decreased to 71 with a standard deviation of 2.204. Seeing the effectiveness of acupressure therapy in lowering blood pressure in hypertensive patients, this therapy can be applied as a non-pharmacological treatment for patients who experience high blood pressure. Keywords: Acupressure, blood pressure, hypertension